Construction Contracting Management Obstacles in Palestine - shweiki, inas (My University, 2013)
The construction industry is complex, widely varying and many factors influencing its projects outcome. As construction projects become larger and more complex, their management and challenges become more complicated and core element for success. During the past few years, many of the construction projects in West Bank went beyond timeline with extra cost overruns, many obstacles faced the contracting process and generally, the contracting career failed to take what it deserved of commensurate development. The objectives of this research are to study the construction contracting sector in Palestine, highlight this sector problems and obstacles from the perspective of local contract parties; project owners, consultants, contractors and donor countries institutes. In addition to, investigate the importance of these problems and observe identical situations in other neighboring Arab countries, in order to investigate some proposed solutions for improving the current sector situation. In order to achieve this research objectives, set of interviews were held with some contract parties to survey the problems they experience. Also, a questionnaire was performed to assess the importance degree of these problems. Results from the study showed that the problems related to the career ethics are the most important problems that the Palestinian construction sector suffers from. Also, results showed that the major construction contracting problems are: Intense competition between contractors to the extent of bidding at cost prices or by losses, policy adoption of awarding the tender to the lowest evaluated bidder not to the most accurate, owners' payments delay, currency exchange rate fluctuation, owner deceleration in decision making, the number of available contractors is high compared with the size of tendered projects, fluctuation of construction materials prices due to inflation, current economic situation deterioration, some contractors maneuvers by downloading some prices on other items and conflicts between tender documents. Based on these findings, proposed solutions were developed for solving and improving the current state. Proposed solutions were presented in a framework to solve and avoid the negative impact of such problems which might improve the performance of construction sector in Palestine. Finally, recommendations for the PNA, PCU and the other related contract parties were presented in this research helping them in overcoming the current sector related obstacles.
Keywords: Construction Management; Contracting management